Enhancing Maritime Cargo Documentation with Blockchain Technology - Mudakir; Retno Sawitri Wulandari; Larsen Barasa; Dwiyani, Nurindah; Titis Ari Wibowo (LPPM POLITEKNIK LP3I BANDUNG, 2024)
This research explores the potential of blockchain technology to streamline multimodal cargo documentation in the maritime industry. Through qualitative analysis of 100 cadets at the Maritime Institute, key indicators including efficiency, security, interoperability, and readiness for adoption were identified and weighted. Findings show that security and efficiency are paramount, with participants highlighting the need for secure and streamlined documentation processes. Interoperability and readiness for adoption emerged as challenges, indicating the importance of industry-wide standards and training programs. The study underscores the critical role of standardisation in supporting the adoption of blockchain solutions and improving international transportation processes. By addressing these challenges, stakeholders can enhance the security, efficiency, and interoperability of cargo documentation processes, ultimately benefiting the maritime industry.